1997
DOI: 10.1046/j.1469-8137.1997.00825.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis and physiology of a trait for enhanced K+/Na+ discrimination in wheat

Abstract: SUMMARYVariation for K" and Na^ accumulation at low salinities in hydroponic (water) culture were observed in shoots of different wheat species. Greater discrimination (in favour of K+ and against Na+ accumulation) was shown by hexaploid bread wheat {Triticum aestivum L.) than by tetraploid durum wheat (T. turgidum L.). Since Aegilops tauschii Cosson {A. squarrosa L.), the source of the D genome in bread wheat, also exhibited high discrimination between K"^ and Na^, it was concluded that the character resided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(52 citation statements)
references
References 28 publications
(24 reference statements)
1
49
2
Order By: Relevance
“…Eventually this adaptability was concluded to be a multigenetic trait that defied simple genetic introgression. Later, studies with rice confirmed the multigenic basis of tolerance responses but also indicated that substantial tolerance may be mediated by just a few genes (Gorham et al, 1997). Evidence that single genes could affect tolerance to osmotic stress continued to appear sporadically from the 1960s through the 1980s.…”
Section: On the Genetics Road: Aristotle Meets Arabidopsismentioning
confidence: 83%
“…Eventually this adaptability was concluded to be a multigenetic trait that defied simple genetic introgression. Later, studies with rice confirmed the multigenic basis of tolerance responses but also indicated that substantial tolerance may be mediated by just a few genes (Gorham et al, 1997). Evidence that single genes could affect tolerance to osmotic stress continued to appear sporadically from the 1960s through the 1980s.…”
Section: On the Genetics Road: Aristotle Meets Arabidopsismentioning
confidence: 83%
“…The important control mechanism under salt stress is the high K ' / Na ' selectivity in plants. It has been suggested to be an important selection criterion for salt tolerance (Rains 1972;Flowers et al 1977;Greenway and Munns 1980;Gorham et al 1997;Ashraf 2002;Wenxue et al 2003). A similar trend has been reported in present study with respect to Na ' and K ' content in leaf ( Figure 5).…”
Section: Resultsmentioning
confidence: 99%
“…Potassium is the major inorganic constituent of plant cells (Abebe et al, 2003) and is involved in many physiological processes including regulation of turgor potential, cell elongation, and stomatal movement (Meneguzzo and Navari-Izzo, 2000;Rascio et al, 2001). A proper K + : Na + ratio is vital for the adjustment of cell osmoregulation, activation of enzymes, oxidant metabolism, and photosynthesis (Gorham et al, 1997;Shabala et al, 2003).…”
Section: Introductionmentioning
confidence: 99%